<h2>Answer = </h2><h2>
![= \frac{1}{y {}^{5} x {}^{2} }](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B1%7D%7By%20%7B%7D%5E%7B5%7D%20x%20%7B%7D%5E%7B2%7D%20%7D%20)
</h2>
Step-by-step explanation:
Greetings !
simplify for variable y first
apply exponent rule
![a {}^{b} .a {}^{c} = a {}^{b +c \\ } \\ y {}^{ - 8}y {}^{5} = y {}^{ - 8 + 3}](https://tex.z-dn.net/?f=a%20%7B%7D%5E%7Bb%7D%20.a%20%7B%7D%5E%7Bc%7D%20%20%3D%20a%20%7B%7D%5E%7Bb%20%2Bc%20%5C%5C%20%20%20%7D%20%5C%5C%20%20y%20%7B%7D%5E%7B%20-%208%7Dy%20%7B%7D%5E%7B5%7D%20%20%3D%20y%20%7B%7D%5E%7B%20-%208%20%2B%203%7D%20)
Add/subtract the numbers -8+3=5
![= y {}^{5}](https://tex.z-dn.net/?f=%20%3D%20y%20%7B%7D%5E%7B5%7D%20)
Apply exponent rule
![a {}^{ - b} = \frac{1}{a {}^{b} }](https://tex.z-dn.net/?f=a%20%7B%7D%5E%7B%20-%20b%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7Ba%20%7B%7D%5E%7Bb%7D%20%7D%20)
Thus,
![y {}^{ - 5} = \frac{1}{y {}^{5} }](https://tex.z-dn.net/?f=y%20%7B%7D%5E%7B%20-%205%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7By%20%7B%7D%5E%7B5%7D%20%7D%20)
secondly, simplify for the variable x
Apply exponent rule as we made on y
![x {}^{ - 2}](https://tex.z-dn.net/?f=x%20%7B%7D%5E%7B%20-%202%7D%20)
![x {}^{ - 2} = \frac{1}{x {}^{2} }](https://tex.z-dn.net/?f=x%20%20%7B%7D%5E%7B%20-%202%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7Bx%20%7B%7D%5E%7B2%7D%20%7D%20)
multiply bot the values we get
Hope it helps!
Answer:
69
Step-by-step explanation:
The answer is 3x^2-19x+1
(-4x+3)-(7x-3x^2-1)
-12x+7x+3x^2+1
Combine like terms:
3x^2+(-12x+-7x)+1
= 3x^2+-19x+1
Answer:
K, (-3.5,-5), E, (3.5, 3)
Step-by-step explanation:
To find the original length you must take away the add-ons. To do so we know that they added 7 and A= l*l (or l squared). They added the 7 to the length so multiply 7*7 (49) subtract your answer from 169 (120) and that's your new area. To find the original length divide by 4 (I believe) and get 30m2